Abolir les passeports ? Les gouvernements contre l’opinion - Speranta Dumitru (Cahiers d’histoire)
The international system of obligatory passports, as it exists today, was established at the beginning of the First World War. After the Armistice, the League of Nations tried to abolish it, but several governments delayed it. This article analyzes how the French press of the interwar period called for the abolition of passports. Seen as a "vexation", the passport was deemed "useless" after the war. So why wasn’t it abolished? Among the reasons for maintaining passports, we explore the hypothesis of political “utility”: the regime of obligatory passports enabled governments to refuse passports and thus to control the transnational activity of political opponents.